Pengaruh Puasa Senin Kamis Terhadap Kecerdasan Emosional Santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor - Hasanatunnisa, Luluwatul; Fahmi Irfani; Noneng Rosidah (Jurnal Dirosah Islamiyah, 2024)
This study was conducted with several objectives, namely: 1) to determine how much the level of intensity of fasting Sunnah Monday Thursday santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor, 2) to determine the emotional intelligence of santriwati Class XI and XII at Pondok Pesantren Miftahul Huda Bantar Kambing Bogor, 3) explain the effect of fasting sunnah Monday Thursday to emotional intelligence santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor. The type of research method used in this study is a quantitative approach research method. The method used is the survey method. The techniques used are observation, questionnaire, and documentation. The number of respondents used in the study were 59 santriwati. This study in data analysis techniques using linear Regression Test. The results showed that: 1) the level of keistiqomahan fasting Monday and Thursday students of Pondok pesantren Miftahul Huda Bantar Kambing Bogor have the results of the percentage of 85% which is at the level of 76% -85% interval in the good category. So it can be concluded that the level of intesnsitas fasting Monday Thursday santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor is classified as good, 2) the level of emotional intelligence santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor has an average percentage of 80% which is included in the good category. So it can be drawn a common thread that the level of emotional intelligence santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor is high, 3) fasting Monday and Thursday significantly affect the emotional intelligence santriwati Pondok Pesantren Miftahul Huda Bantar Kambing Bogor. The effect of fasting on Monday and Thursday is 27.8% while the remaining 72.2% is influenced by other variables/factors that were not studied. Showed that there is a significant influence between fasting Monday and Thursday (X) and emotional intelligence (Y) and both have positive (+) or unidirectional influence.